The nature of the Syntaxin4 C-terminus affects Munc18c-supported SNARE assembly - Rehman, Asma (PLoS One, 2017)
Vesicular transport of cellular cargo requires targeted membrane fusion and formation of a SNARE protein complex that draws the two apposing fusing membranes together. Insulin-regulated delivery and fusion of glucose transporter-4 storage vesicles at the cell surface is dependent on two key proteins: the SNARE integral membrane protein Syntaxin4 (Sx4) and the soluble regulatory protein Munc18c. Many reported in vitro studies of Munc18c:Sx4 interactions and of SNARE complex formation have used soluble Sx4 constructs lacking the native transmembrane domain. As a consequence, the importance of the Sx4 C-terminal anchor remains poorly understood. Here we show that soluble C-terminally truncated Sx4 dissociates more rapidly from Munc18c than Sx4 where the C-terminal transmembrane domain is replaced with a T4-lysozyme fusion. We also show that Munc18c appears to inhibit SNARE complex formation when soluble C-terminally truncated Sx4 is used but does not inhibit SNARE complex formation when Sx4 is C-terminally anchored (by a C-terminal His-tag bound to resin, by a C-terminal T4L fusion or by the native C-terminal transmembrane domain in detergent micelles). We conclude that the C-terminus of Sx4 is critical for its interaction with Munc18c, and that the reported inhibitory role of Munc18c may be an artifact of experimental design. These results support the notion that a primary role of Munc18c is to support SNARE complex formation and membrane fusion.